Analisis Perancangan Antena Microstrip Planar Array Rectangular Patch untuk Frekuensi Radar: Telekomunikasi Militer - Imam Ashar; Desyderius Minggu; Ananda Herdi Akbar (Pustaka Poltekad, 2026)
This study aims to design and analyze a Rectangular Patch Planar Array Microstrip Antenna for radar frequency applications. The results of the analysis and design indicate that the proposed Rectangular Patch Planar Array Microstrip Antenna, based on calculations using empirical formulas, is capable of operating at radar frequencies. The microstrip antenna operates within the Ultra Wide Band (UWB) range and achieves a resonant frequency of 1.5 GHz with an antenna gain of 8.70 dB. In addition, the obtained Voltage Standing Wave Ratio (VSWR) value is 1.44.